1990
DOI: 10.1159/000115865
|View full text |Cite
|
Sign up to set email alerts
|

Configuration-Sensitive Visual Responses in the Superior Colliculus of the House Mouse <i>(Mus musculus domesticus</i><i>)</i>

Abstract: In order to compare visual pattern discrimination by tectal neurons in distantly related vertebrate groups, collicular cells of mice were examined for their responses to each of three simple configurational stimuli commonly used in studies of amphibians. The stimuli consisted of a large square, a horizontal bar and a vertical bar moved at various velocities. Of the recorded units (n = 51), 30–50% significantly preferred the square to the other stimuli at medium (10°/s) and high (67°/s) velocities. Approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The neural pathways involved have been also determined (Keay et al, 1990;Redgrave et al, 1987Redgrave et al, , 1988Redgrave et al, , 1990Redgrave et al, , 1993 and they seem to be similar to those present in anurans (Sewards and Sewards, 2002), indicating a remarkable conservation of functions among different phyla of vertebrates. This is further confirmed in experiments with mice, whose collicular cells responded to each of the three simple visual configurations commonly used in studies of amphibian prey and predator recognition (Ewert, 1987;Ewert and von Wietersheim, 1974;Manteuffel and Fiseifis, 1990;Matsumoto et al, 1986). These stimuli consisted of a large square, a horizontal bar and a vertical bar moved at various velocities.…”
Section: Neuronal Bases Of Social Predispositionssupporting
confidence: 54%
See 1 more Smart Citation
“…The neural pathways involved have been also determined (Keay et al, 1990;Redgrave et al, 1987Redgrave et al, , 1988Redgrave et al, , 1990Redgrave et al, , 1993 and they seem to be similar to those present in anurans (Sewards and Sewards, 2002), indicating a remarkable conservation of functions among different phyla of vertebrates. This is further confirmed in experiments with mice, whose collicular cells responded to each of the three simple visual configurations commonly used in studies of amphibian prey and predator recognition (Ewert, 1987;Ewert and von Wietersheim, 1974;Manteuffel and Fiseifis, 1990;Matsumoto et al, 1986). These stimuli consisted of a large square, a horizontal bar and a vertical bar moved at various velocities.…”
Section: Neuronal Bases Of Social Predispositionssupporting
confidence: 54%
“…These stimuli consisted of a large square, a horizontal bar and a vertical bar moved at various velocities. Because of the similarity of the responses, it has been concluded that tectal configurational sensitivity may be a plesiomorphic tetrapod character resulting from basic properties of tectal neuronal circuitry (Manteuffel and Fiseifis, 1990).…”
Section: Neuronal Bases Of Social Predispositionsmentioning
confidence: 99%
“…Manteuffel and Fiseifis (1990) have recently shown that a similar configurational selectivity which is dependent on the stimulus velocity is also observed in mouse tectal neurons and concluded that the velocitydependent configurational selectivity of the tectal neurons is not specific to the toad but is a more general character resulting from basic properties of the tectal neuronal circuitry.…”
Section: Tectal Neurons As 'Local Motion Detectors'mentioning
confidence: 77%